LARGEST SPECIMEN OF BIG-JAWED JUMPER, LACTARIUS LACTARIUS (SCHNEIDER) - Shanmugavelu, C R (Indian Journal of Fisheries, 2011)
A specimen of Lactarius lactarius 330 mm total length was recorded froma drift net catch at Pamban (Gulf of Mannar). The largest specimen of thisspecies recorded so far had only 23 rays in the anal fin as against 72-28 raysin the normal specimens.